Water-organic mixed electrolyte and preparation method and application thereof
By using water-organic hybrid electrolyte in water-based lithium-ion batteries, using lithium salts, organic solvents and electrolyte additives, the problem of narrow electrochemical stability window of water-based lithium-ion batteries is solved, and high energy density and cycle stability are achieved Battery performance.
Patent Information
- Application Number
- CN202411590202.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
Due to the narrow window of electrochemical stability of water lithium-ion batteries, the operating voltage and energy density are limited, and their wide application and development are hindered.
Using water-organic mixed electrolyte, expand the electrochemical stability window by adding lithium salt, water, organic solvents (such as tetramethylurea or dimethyl sulfoxide) to the electrolyte solution. .
The electrochemical stability window is effectively expanded, the energy density and cycle stability of the battery are improved, and high output voltage and high energy density are achieved.
Smart Images

Figure CN119481353A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a water-organic mixed electrolyte and a preparation method and application thereof, belonging to the technical field of battery water system electrolytes. Background Art
[0002] With the development of economy and society, people's demand for storing intermittent energy (solar energy, tidal energy, wind energy, etc.) is increasing, which has promoted the development of grid-scale energy storage technology. Although lithium-ion batteries with efficient and reversible energy storage have achieved great commercial success, the safety issues that may be caused by the flammability and toxicity of organic electrolytes used in lithium-ion batteries have hindered their further deployment in grid-scale energy storage. Rechargeable lithium-ion batteries based on aqueous electrolytes have attracted widespread attention due to their inherent safety, cost-effectiveness and eco-friendliness. However, the narrow electrochemical stability window of water itself (1.23V) greatly limits the operating voltage and energy density of aqueous lithium-ion batteries, hindering the widespread application and development of aqueous lithium-ion batteries. Although the electrochemical stability window of aqueous electrolytes can be higher than the theoretical value due to the influence of pH and polarization, it is always lower than 1.8V. Many high-potential positive electrode materials (lithium manganate LiMn2O4) and low-potential negative electrode materials (lithium titanate Li4Ti5O 12 ) cannot be used in aqueous lithium-ion batteries.
[0003] In recent years, with the introduction of the "salt-in-water" electrolyte strategy (Science, 2015, 350, 938-943), the electrochemical stability window of water has expanded from 1.23V to 3.0V, which means that the key voltage limit of aqueous lithium-ion battery research has been broken through, providing new research ideas for the design and research of aqueous electrolytes. In this high-concentration salt electrolyte system, by reducing the activity of water, the anion bistrifluoromethanesulfonimide ion (TFSI) in the lithium salt can be used to generate a large amount of water. - ) is reduced on the electrode surface to form a solid electrolyte interface film (SEI film) mainly composed of LiF, which effectively inhibits the hydrogen evolution side reaction and kinetically expands the electrochemical stability window of the aqueous electrolyte. In addition, by adding organic co-solvents (such as dimethyl carbonate, dimethyl sulfoxide, polyethylene glycol, cyclopentane sulfone and other hydrogen bond acceptors) to destroy the hydrogen bond grid between water molecules and form new hydrogen bonds, the hydrogen evolution reaction can be thermodynamically inhibited, which can also effectively expand the electrochemical stability window.
[0004] Therefore, it is necessary to use new strategies to develop an aqueous electrolyte with both safety and excellent electrochemical properties to achieve high energy density aqueous lithium-ion batteries. Summary of the invention
[0005] In view of the above shortcomings, the present invention discloses a water-organic mixed electrolyte and its preparation method and application. The present invention is achieved by the following technical means:
[0006] First, the present invention discloses a water-organic mixed electrolyte, comprising:
[0007] Lithium salt, water, organic solvent and electrolyte additives.
[0008] Furthermore, the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(pentafluoroethylsulfonyl imide) or lithium bis(fluorosulfonyl imide).
[0009] Furthermore, the organic solvent is at least one of tetramethylurea or dimethyl sulfoxide.
[0010] Furthermore, the electrolyte additive is formamide.
[0011] Furthermore, the total molar concentration of the lithium salt is 6.7-14.5m; and the molar ratio of water to the organic solvent is 7.9:5.5-10.6.
[0012] Secondly, the present invention also discloses a method for preparing a water-organic mixed electrolyte, comprising:
[0013] (1) dissolving a lithium salt in water to obtain a first solution;
[0014] (2) dissolving a lithium salt in an organic solvent to obtain a second solution;
[0015] (3) mixing the first solution with the second solution to obtain a third solution;
[0016] (4) Adding an electrolyte additive to the third solution to obtain a water-organic mixed electrolyte.
[0017] Furthermore, in step (1), the first solution is a saturated aqueous solution containing a lithium salt; when the lithium salt is lithium bis(trifluoromethanesulfonyl imide), the concentration of the first solution is 21 m(mol kg -1 水 ).
[0018] Furthermore, when the organic solvent in step (2) is tetramethylurea, the concentration of the second solution is 5m, 7m, 11m, 13m (mol kg -1 四甲基脲 ).
[0019] Furthermore, in step (3), the mass ratio of the first solution to the second solution is 1:3.
[0020] Furthermore, the electrolyte additive in step (4) is 5% of the mass of the third solution.
[0021] The invention also discloses a water-organic mixed electrolyte prepared according to any one of the above preparation methods.
[0022] The present invention also discloses an application of the water-organic mixed electrolyte in preparing an aqueous high-voltage lithium-ion battery.
[0023] Furthermore, the positive electrode active material of the aqueous high-voltage lithium-ion battery is selected from any one of LiCoO2, LiMn2O4 and LiFePO4; the negative electrode active material of the aqueous high-voltage lithium-ion battery is selected from any one of Mo6S8, TiO2 and Li4Ti5O 12 Any one of .
[0024] Furthermore, the assembly steps of the aqueous high-voltage lithium-ion battery are as follows:
[0025] The electrode plate, aqueous electrolyte, gasket and spring are placed in the 2032 button battery in the order of negative electrode shell-spring-gasket-negative electrode plate-electrolyte-diaphragm-electrolyte-positive electrode plate-positive electrode shell, assembled into a full battery, and then the battery is compacted and fastened with a tablet press to obtain a test battery. The model of the separator is glass fiber GF / F.
[0026] The aqueous high-voltage lithium-ion battery provided by the present invention has a higher output voltage (>2V) and a higher energy density (>70Wh kg -1 ).
[0027] The beneficial effects of the present invention are:
[0028] (1) In the present invention, firstly, an aqueous solution containing a lithium salt is mixed with a tetramethylurea solution containing a lithium salt. A higher concentration of lithium salt can surround water and reduce the content of free water, thereby weakening the hydrogen evolution side reaction. At the same time, the tetramethylurea molecules (DN=31) with a high donor number in the mixed electrolyte have a relatively high binding energy with lithium ions and can enter the first solvation shell of lithium ions together with the anions of the lithium salt. This can not only enhance the lithium ion reaction kinetics of the electrolyte, but also can construct a layer of LiF, Li2O, LiO2 and LiO2 at the negative electrode interface with the anions of the lithium salt. x The organic-inorganic double-layer SEI film with N as the main component prevents water from directly contacting the negative electrode surface, causing hydrogen evolution side reactions and electrode dissolution. In addition, the two hydrophobic groups -N(CH3)2 on the tetramethylurea molecule can also exclude water around the solvation shell through steric hindrance effects and prevent water from contacting the negative electrode surface. Under the synergistic effect of these beneficial effects, not only the electrochemical stability window of the electrolyte is widened, the energy density of the battery is improved, but also the cycle stability of the battery is enhanced.
[0029] (2) The present invention adds 5 mass percent of formamide to the above-mentioned mixed solution through preferred control. The donor number of formamide (DN=24) is lower than that of tetramethylurea and higher than that of water (DN=18). On the one hand, formamide, which has both hydrogen bond acceptors and hydrogen bond donors, can replace part of the water molecules to form new hydrogen bonds, adjust the network structure of water, and stabilize the electrolyte; on the other hand, formamide can also form an in-situ barrier between tetramethylurea molecules and water molecules with moderate binding ability to stabilize the electrolyte. More importantly, the formamide solvent with strong polarity has good solubility for lithium salts, which can appropriately reduce the viscosity of the electrolyte caused by the concentration of lithium salts and improve the migration kinetics of lithium ions. The use of additives effectively improves the coulombic efficiency of the whole battery and enhances the electrochemical performance of the battery.
[0030] (3) Li4Ti5O constructed by the water-organic mixed electrolyte of the present invention 12 ||LiMn2O4 lithium-ion battery, the first reversible charge and discharge capacity at room temperature and 1C current density is about 161mAh g -1 , the decay rate per cycle is about 0.15%, and the average coulombic efficiency is 88%. In the presence of additives, the decay rate of the battery per cycle is about 0.19%, and the average coulombic efficiency is 95%, showing better electrochemical performance.
[0031] (4) The preparation process of the mixed electrolyte of the present invention is simple, conventional equipment is used, raw materials are easily available, and it is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the reduction potential of the mixed electrolyte prepared in Comparative Example 1 and Examples 1-4 of the present invention;
[0033] Figure 2 is the oxidation potential of the mixed electrolyte prepared in Comparative Example 1 and Examples 1-3 of the present invention;
[0034] Figure 3 Li4Ti5O assembled from the mixed electrolyte of Example 5 12 ||Cycling performance of LiMn2O4 full battery at 1C current density;
[0035] Figure 4 Li4Ti5O assembled from the mixed electrolyte of Example 1 12 ||Cycling performance of LiMn2O4 full battery at 1C current density;
[0036] Figure 5 Li4Ti5O assembled from the mixed electrolyte of Example 3 12 ||Cycling performance of LiMn2O4 full battery at 1C current density;
[0037] Figure 6 Li4Ti5O assembled from the mixed electrolyte of Example 4 12 ||Cycling performance of LiMn2O4 full battery at 1C current density;
[0038] Figure 7 Li4Ti5O assembled using the mixed electrolyte of Example 4 12 ||Charge and discharge curves of LiMn2O4 full battery at 1C current density. DETAILED DESCRIPTION
[0039] The present invention is further described below by combining examples and drawings. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following examples.
[0040] Example 1
[0041] A method for preparing a water-organic mixed electrolyte
[0042] First, add 21 mol of LiTFSI into 1 kg of deionized water to obtain 21 m (mol kg -1 溶剂 ) aqueous solution; then add 11 mol of LiTFSI to 1 kg of tetramethylurea solution, heat and stir in an 80°C oil bath to dissolve, and obtain 11 m of organic solution; finally, mix the two solutions in a mass ratio of 1:3 to obtain a water-organic mixed electrolyte with a total lithium salt concentration of 12.6 m. Among them, the molar ratio of lithium salt, tetramethylurea, and water is 10.9:6.2:7.9.
[0043] Example 2
[0044] In this example, a water-organic mixed electrolyte was prepared in the same manner as in Example 1, except that 5 mol of LiTFSI was added to 1 kg of tetramethylurea solution to obtain a 5 m organic solution. The total concentration of lithium salt in the mixed electrolyte of this example was 6.7 m. The molar ratio of lithium salt, tetramethylurea, and water was 9.1:10.6:7.9.
[0045] Example 3
[0046] In this example, a water-organic mixed electrolyte was prepared in the same manner as in Example 1, except that 13 mol of LiTFSI was added to 1 kg of tetramethylurea solution to obtain a 13 m organic solution. The total lithium salt concentration of the mixed electrolyte in this example was 14.5 m. The molar ratio of lithium salt, tetramethylurea, and water was 11.22:5.5:7.9.
[0047] Example 4
[0048] In this example, 5% by weight of formamide additive is added to the solution prepared in Example 1.
[0049] Comparative Example 1
[0050] This comparative example is to add 21 mol of LiTFSI into 1 kg of deionized water to obtain 21 m (mol kg -1 溶剂 ) aqueous electrolyte. The molar ratio of lithium salt to water is 1:2.65.
[0051] The electrolytes prepared in all the above examples and comparative examples were subjected to electrochemical window tests. The tests were conducted using a CHI 660 (Shanghai Chenhua) electrochemical workstation, with Al (negative electrode) and Ti (positive electrode) as the working electrodes, carbon cloth as the counter electrode, Ag / AgCl as the reference electrode, and a scan rate of 10 mV s -1 .
[0052] Depend on Figure 1 It can be seen that compared with comparative example 1, the reduction potentials of examples 1-4 in the present invention are significantly shifted to a lower direction, indicating that the hydrogen evolution reaction is effectively suppressed. Especially after the addition of the additive, a more stable window is shown. This may be because formamide has both hydrogen bond donors and hydrogen bond acceptors, and combined with a stronger electronegativity than water molecules, it can participate in the hydrogen bond grid of water to form new molecular hydrogen bonds, thereby suppressing the activity of water. Figure 2 It can be seen that compared with Comparative Example 1, the greater the molar ratio of tetramethyl urea to water in the mixed solution, the smaller the oxidation potential, which may be because tetramethyl urea molecules are easily oxidized and decomposed.
[0053] Example 5
[0054] In this example, a water-organic mixed electrolyte was prepared in the same manner as in Example 1, except that 7 mol of LiTFSI was added to 1 kg of tetramethylurea solution to obtain a 7 m organic solution. The total lithium salt concentration of the mixed electrolyte in this example was 8.8 m. The molar ratio of lithium salt, tetramethylurea, and water was 9.97:8.6:7.9.
[0055] Example 6
[0056] The embodiment of the present invention provides a water-organic hybrid lithium ion battery, wherein the water-organic hybrid electrolyte is prepared by the embodiment 1, the embodiment 3 and the embodiment 4, and the negative electrode is Li4Ti5O 12 The positive electrode is LiMn2O4. The preparation process of the electrode is as follows: first, the active component (Li4Ti5O 12Or LiMn2O4), conductive carbon black (Super-P), and binder (PVDF) are mixed evenly in a mass ratio of 8:1:1; then a certain amount of solvent NMP is added to form a slurry, which is coated on carbon-coated aluminum foil and baked at 100°C overnight; finally, it is cut into small discs with a diameter of 12 mm for use. The separator is glass fiber GF / F.
[0057] Depend on Figure 3-5 It can be seen that the Li4Ti5O 12 ||The capacity retention rate of the LiMn2O4 battery after 200 cycles at a current density of 1C was approximately 70%, 54% and 66%, respectively, and the average coulomb efficiency was 88%, 91% and 91%, which shows that the inorganic-organic double-layer SEI generated by the electrolyte in Example 1 at the electrode interface is more stable, thus ensuring a good cycle stability of the whole battery. However, the coulomb efficiency is relatively low, which may be related to the hydrogen evolution reaction, and the SEI film and electrochemical stability window need to be further optimized.
[0058] By selecting formamide molecules with a DN value between tetramethylurea and water, water molecules are further and more comprehensively prevented from entering the first solvation shell. At the same time, its hydrogen bond donors and hydrogen bond acceptors can also destroy the original hydrogen bond grid and form new hydrogen bonds to inhibit the activity of water. Figure 6 and Figure 7 As shown, Li4Ti5O prepared by the electrolyte prepared in Example 4 12 ||LiMn2O4 battery outputs an average voltage of up to 2.25V at a current density of 1C, and the charge and discharge capacity in the first week is about 161mAh g -1 The average coulombic efficiency is about 95%, which has good reversibility, indicating that formamide effectively inhibits the activity of water by replacing water molecules to form new hydrogen bonds, stabilizes the SEI film at the electrode interface, and improves the Li4Ti5O 12 ||Electrochemical performance of LiMn2O4 full cell.
[0059] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A water-organic mixed electrolyte comprising: Lithium salts, water, organic solvents and electrolyte additives; The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(pentafluoroethylsulfonyl imide) or lithium bis(fluorosulfonyl imide); The organic solvent is at least one of tetramethylurea or dimethyl sulfoxide; The electrolyte additive is formamide; wherein: The total molar concentration of the lithium salt is 6.7-14.5m; the molar ratio of the water to the organic solvent is 7.9:5.5-10.
6.
2. A method for preparing the water-organic mixed electrolyte according to claim 1, comprising: (1) dissolving a lithium salt in water to obtain a first solution; (2) dissolving a lithium salt in an organic solvent to obtain a second solution; (3) mixing the first solution and the second solution in a mass ratio of 1:3 to obtain a third solution; (4) Adding an electrolyte additive to the third solution to obtain a water-organic mixed electrolyte.
3. The preparation method according to claim 2, wherein: Step (1) The first solution is a saturated aqueous solution containing a lithium salt; when the lithium salt is lithium bis(trifluoromethanesulfonyl imide), the concentration of the first solution is 21 m(mol kg -1 水 ).
4. The preparation method according to claim 2, wherein: When the organic solvent in step (2) is tetramethylurea, the concentration of the second solution is 5m, 7m, 11m, 13m (mol kg -1 四甲基脲 ).
5. The preparation method according to claim 2, wherein: The electrolyte additive in step (4) is 5% of the mass of the third solution.
6. A water-organic mixed electrolyte prepared according to any one of the preparation methods of claims 2 to 5.
7. Use of the water-organic mixed electrolyte according to claim 1 or 6 in the preparation of an aqueous high-voltage lithium-ion battery.
8. The use according to claim 7, wherein: The positive electrode active material of the aqueous high-voltage lithium-ion battery is selected from any one of LiCoO2, LiMn2O4 and LiFePO4; The negative electrode active material of the aqueous high-voltage lithium-ion battery is selected from: Mo6S8, TiO2 and Li4Ti5O 12 Any one of .
9. The use according to claim 7, wherein: The assembly steps of the aqueous high-voltage lithium-ion battery are as follows: The electrode plates, aqueous electrolyte, gaskets and shrapnel are placed into a 2032 button battery in the order of negative electrode shell-shrapnel-gasket-negative electrode plate-electrolyte-diaphragm-electrolyte-positive electrode plate-positive electrode shell to assemble into a full battery, and then the battery is compacted and fastened with a tablet press to obtain a test battery; the model of the diaphragm is glass fiber GF / F.
10. The use according to claim 9, wherein: The output voltage of the aqueous high-voltage lithium-ion battery is >2V, and the energy density is >70Wh kg -1 .